Design of an electronic control system for automating the GMAW welding process - Taufik Fajar; Rafge Cahya Pramana; I Wayan Adiyasa (Journal of Automotive and Mechanical Applied Technology, 2025)
This study aims to design and implement an electronic control system to automate the GMAW welding process, focusing on precise regulation of travel speed and travel length to improve repeatability, safety, and weld consistency. The methodology is organized into four stages: (1) needs analysis to define functional requirements, user constraints, and operating ranges; (2) system design covering hardware architecture, sensor and actuator selection, and embedded control logic; (3) implementation through microcontroller-based integration of a motion drive, user interface, and parameter-setting features; and (4) testing to verify accuracy, stability, and performance under realistic operating conditions. The results demonstrate that the system regulates welding speed with an accuracy of 92.54%–99.44%, while maintaining a maximum time standard deviation of 0.038 seconds, indicating stable motion over repeated trials. For welding length control, the system achieves an average absolute error of 0.35–0.5 mm, a percentage error of 0.17%–0.7%, and a standard deviation of 0.051 mm or less, supporting consistent endpoint positioning. In real-world welding tests, the actual weld length deviation ranges from 0.20 to 1.71 mm. It remains within ISO 13920 Class D tolerance limits, confirming practical applicability for general fabrication. The developed controller enables precise parameter control over a speed range of 100–800 mm/min and a length range of 50–300 mm, reducing the need for direct operator intervention and limiting human-induced variability. Overall, the system supports safer, more consistent welding operations and provides a scalable platform for integrating additional monitoring or adaptive control functions. Suitable for training, prototyping, and routine production trials. Future work will address adaptive control diagnostics.